Pharmacy Education: Preparing Pharmacists for Global Challenges in the Digital Age - Amin, Saeful; Fadli, Fadli; Justicia, Adhisty Kharisma (Journal of Pharmacopoeia, 2025)
This study aims to examine the development of pharmacy education in the digital era, as well as to prepare pharmacists to face global challenges. The method used is the Systematic Literature Review (SLR), which is carried out by collecting, evaluating, and synthesizing previous research results comprehensively. The research process includes identifying literature through academic databases such as Scopus, PubMed, Google Scholar, and ScienceDirect, selecting studies based on inclusion and exclusion criteria, extracting data related to objectives, methods, results, and conclusions, synthesizing findings, and reporting research results. The results of the study indicate that pharmacy education needs to transform to prepare competent pharmacists in the digital era. Integration of technology into the curriculum such as e-learning, blended learning, augmented reality (AR), and virtual reality (VR) provides a more flexible learning experience. In addition, mastery of technology such as big data, artificial intelligence (AI), and pharmacy information systems is essential to support evidence-based decision making and efficiency of health services. The challenges faced include limited infrastructure, resistance to change, and the gap between the competencies taught and the digital skills needed in the world of work. Therefore, curriculum updates and training for pharmacists who are already working are very necessary to ensure pharmacists are prepared to face an increasingly digitalized profession